The Implementation of Writing Thank-You Letters to Enhance Subjective Well-Being Among Elementary School Students: Penerapan Menulis Thank You Letters dalam Meningkatkan Subjective Well-Being pada Anak Sekolah Dasar - Sukma Ainul Fitri; Karinta Elmira Amalia; Dita Padiani Rahma; Muflihatul Awalyah; Pinasthika Kautsari Pradipta; Alfaiz Alfaiz; Fitri Ariyanti Abidin; Fitriani Yustikasari Lubis (Institut Riset dan Publikasi Indonesia, 2026)
Subjective well-being (SWB) is important for children’s development, yet emotional challenges in elementary school can reduce students’ quality of life. This study aimed to improve SWB through a Writing Thank-You Letters intervention using a pre-experimental one-group pretest–posttest design. Participants were 44 fourth-grade students of SD Al-Ma’soem Bandung. PANAS-C measured SWB, and GQ-6 assessed gratitude. Data were analyzed using Repeated Measures ANOVA with Bonferroni-corrected pairwise comparisons. Results showed a significant increase in positive affect (p < 0.001), while negative affect and gratitude were not significant in the long term. However, initial trends indicated improvement, with decreased negative affect (M = 39.36 to 38.00) and increased gratitude (M = 26.64 to 27.86). This intervention can serve as a reflective activity to refresh students’ emotional states. Regular implementation is recommended to strengthen long-term SWB and gratitude.